Metabolomic characteristics of cord blood from neonates with hyperkalemia after antenatal exposure to ritodrine and magnesium sulfate - Masanori Inoue; Kazuhito Sekiguchi; Haruka Tsushita; Naomi Inoue; Tomoki Maeda; Hiroki Itoh; Kenji Ihara (Scientific Reports)
Abstract In the management of pregnancy, ritodrine has been used to prevent preterm birth, and magnesium sulfate (MgSO4) has been used to prevent preterm labor and preeclampsia. Neonates born to mothers receiving these medications occasionally show an increase in serum potassium concentration. Recently, an elevated risk of neonatal hyperkalemia has been reported, particularly when ritodrine and MgSO4 are co-administered; however, the underlying mechanisms remain unclear. We conducted a retrospective cohort study of 142 preterm infants born between 24 and 36 weeks of gestation, categorized into groups exposed to antenatal ritodrine, MgSO4, both agents, or neither. In addition, we investigated the association between potassium levels and metabolites in the serum of umbilical cord blood from 33 infants exposed to antenatal ritodrine and MgSO4 using a metabolomic analysis. Our findings revealed a significant elevation in serum potassium concentration associated with metabolomic findings of activation of glycolysis and the derived metabolic routes in preterm neonates exposed to both ritodrine and MgSO4. Our data indicate that the concurrent administration of ritodrine and MgSO4 caused distinctive metabolic alterations, potentially leading to an additional increase in the intracellular potassium concentration in the fetus. Consequently, this mechanism may imply an elevation in serum potassium concentration postnatally through the redistribution of potassium.